Layered Titanium-Based Materials Manufactured with Cast and Wrought: Production, Composition, Microstructure, and Mechanical Properties - P.E. Markovsky, S.V. Akhonin, V.O. Berezos, O.O. Stasiuk, V.I. Bondarchuk, D.V. Oryshych, Ye.I. Lipchanchuk, and O.V. Zatsarna (Успехи физики металлов)
The features of formation of the structure, composition and certain mechanical properties of layered materials based on titanium and its alloys during melting by the electron-beam cold-hearth melting technique are considered. The influence of composition in two-layer structures Ti64 (Ti–6Al–4V)/LCB (low-cost beta Ti–1.5Al–6.8Mo–4.5Fe) and Ti64/Ti5553 (Ti–5Al–5V–5Mo–3Cr), as well as 4-layer Ti5553/Ti64/c.p.Ti (commercial purity titanium)/Ti64 is studied. The processes of formation of transition layers at the boundaries between alloys after both the smelting and the subsequent deformation by rolling, as well as after heat treatments, are studied. A relationship is established between the composition and the formed microstructure, on the one hand, and hardness, strength, ductility, and fracture under 3-point bending, on the other hand. A comparison of the titanium-layered materials produced by this method with the results provided by other technological approaches is carried out, and the advantages of the proposed technology are shown.